Disentangling COVID-19 vaccine hesitancy: the role of social imaginaries of epidemics in northern Sierra Leone - Yara Alonso; Abu Bakarr Jalloh; Kwabena Owusu-Kyei; Augustin E. Fombah; Clara Menéndez; Mohamed Samai; Cristina Enguita-Fernàndez (SSM: Qualitative Research in Health)
The WHO identified vaccine hesitancy as a threat to global health in 2019, but it was the COVID-19 pandemic that brought it to the fore of public discussions. Despite efforts to account for context in public health frameworks, these fail to translate into analyses that meaningfully capture the local dynamics forging vaccine hesitancy, while dominant public narratives continue to offer decontextualized and monolithic portrayals of this multifaceted phenomenon. Drawing on ethnographic insights from fieldwork conducted in northern Sierra Leone, we propose the notion of ‘social imaginaries of epidemics’ as a socio-historical lens through which to understand how people made sense of the COVID-19 pandemic and the ensuing response, thereby disentangling the shared meanings that enabled vaccine hesitancy in this setting. We do this by reconstructing three key narratives that shaped how COVID-19 was being socially imagined: epidemic memories, mistrust in the governance of epidemics, and diverging health priorities. The social imaginary of COVID-19 as a disease that was ‘deadly’, ‘harmless’, ‘invisible’ or ‘fake’ continuously shifted, yet always in dialogue with shared memories of the last Ebola epidemic. The social imaginary of the COVID-19 response was shaped by existing mistrust in the state's governance of epidemics, whereby the response was underfunded or weak as the result of the government ‘eating COVID money’ or pursuing electoral advantages. The immunisation response was socially imagined as responding to foreign instead of local priorities by disregarding food insecurity in favour of vaccines. Together, this social imaginary rendered COVID-19 vaccines useless, harmful or unimportant to many.